An Unusual Salmonella Enteritidis Strain Carrying a Modified Virulence Plasmid Lacking the prot6e Gene Represents a Geographically Widely Distributed Lineage - Nadin-Davis, Susan; Pope, Louise; Chmara, John; Duceppe, Marc-Olivier; Burke, Teresa; Devenish, John; Andrievskaia, Olga; Allain, Ray; Ogunremi, Dele (Frontiers in Microbiology, 2020)
This study identifies a strain of Salmonella enterica subspecies enterica serovar Enteritidis that harbors a highly unusual virulence plasmid. During the characterisation of a group of S. Enteritidis isolates, 10 isolates recovered from Canadian duck production facilities, of which seven were phage type 9b and three were closely related atypical phage types, failed detection by a PCR targeting the prot6e gene, a marker located on the virulence plasmid often employed for identification of this serovar. Comparison to prot6e+ isolates by several standard genetic typing tools, further revealed their distinctive genomic makeup. Both short read and long read whole genome sequencing were completed on six of these isolates. In addition to loss of the prot6e gene, the virulence plasmid of each isolate was found to be exceptionally large (86.5 Kb) due to a 28Kb insertion of S. Typhimurium plasmid sequence that encodes multiple genes of the incF operon. Interrogation of the chromosome sequence data of these isolates using a SNP-based typing tool and MLST both indicated their close genetic similarity and suggested their highly clonal nature. One additional isolate carrying this plasmid was identified in an in-house collection of S. Enteritidis isolates. Finally, the identification of this unusual plasmid sequence in additional isolates submitted to public repositories of Salmonella sequence data was explored. All these analyses indicated that a very distinctive but rarely reported strain of S. Enteritidis was widely distributed across North America and the United Kingdom with one additional report involving a case from Brazil. With increased use of genetic methods for Salmonella identification, the loss of the prot6e sequence may confound correct identification of this serovar while also potentially altering the mode of transmission to humans given the gene’s role in facilitating propagation of this bacterium in eggs. Accordingly, this strain may present certain challenges with respect to public health investigations. Our studies also suggest this strain is often associated with duck hosts thereby providing a possible mechanism by which this strain has spread over an extensive geographical area.